Decision Support System for Selecting Doorprize Receipt Customers By Applying Promethee I Algorithm - iin - Parlina; Andi Priatno (Universitas Medan Area, 2020)
Door prize is a prize given by Bank Mega Syariah for free through a lottery that has the category of a permanent customer. The permanent customer is a person who saves or saves his money in a mega Islamic bank and often deals regularly. This is what triggers Bank Mega Syariah to give awards to customers so that these customers will be more motivated to save at the Mega Syariah Bank. To determine the right decision in the selection of customers who deserve to get a door prize, then this research was conducted by applying the decision support system method with Promethee's Algorithm.Keywords: Decision Support System, Promethee I, and Doorprize.